SYN-004 (ribaxamase) prevents New Onset Clostridium difficile Infection by Protecting the Integrity Gut Microbiome in a Phase 2b Study. (4th October 2017) - Kokai-Kun, John; Roberts, Tracey; Coughlin, Olivia; Whalen, Heidi; Le, Charles; Da Costa, Christopher; Sliman, Joseph
Abstract: Background: Clostridium difficile infections (CDI) are an "urgent threat, " but there are no approved drugs or vaccines to prevent new onset CDI. SYN-004 (ribaxamase) is a β-lactamase designed to be orally administered with IV β-lactam antibiotics and remain localized in the intestine to degrade antibiotics excreted into the intestine. This is expected to protect the gut microbiome from disruption thus preventing deleterious effects including CDI, colonization by opportunistic pathogens, and emergence of antibiotic resistance in the gut microbiome. Ribaxamase was well tolerated and not systemically absorbed in Phase 1 studies and efficiently degraded ceftriaxone excreted into the human intestine while not altering the plasma pharmacokinetics of ceftriaxone in Phase 2a studies. Methods: A multinational Phase 2b, double-blind, placebo-controlled, study was conducted to determine whether ribaxamase could prevent new onset CDI with additional endpoints for non-CDI antibiotic-associated diarrhea, colonization by opportunistic pathogens, changes in the gut microbiome and emergence of antibiotic resistance. The 412 patient mITT population, enriched for higher risk for CDI, were admitted to the hospital for ≥5 days of IV ceftriaxone for the treatment of a lower respiratory tract infection. Patients were randomized 1:1 to receive ribaxamase or placebo during treatment and for 72h after. Fecal samples were collected at prespecified points for determination of colonization by opportunistic pathogens and to examine changes in the gut microbiome. Patients were monitored for 6 weeks for CDI (diarrhea plus the presence of C. difficile toxin). The study was powered at 80% for the reduction in CDI with 1-sided α = 0.05. Results: The study met its primary endpoint with a 71% relative risk reduction in CDI (1-sided p = 0.045) and had a statistically significant 44% relative risk reduction in new colonization by vancomycin-resistant enterococci (1-sided p = 0.0002). Ribaxamase also protected the diversity of the gut microbiome and reduced the emergence of antibiotic resistance in ceftriaxone-treated patients. Conclusion: These data support that ribaxamase can maintain the balance of the gut microbiome and thereby prevent opportunistic infections like CDI during IV β-lactam treatment. Disclosures: J. Kokai-Kun, Synthetic Biologics, Inc.: Employee, Salary; T. Roberts, Synthetic Biologics, Inc.: Employee, Salary; O. Coughlin, Synthetic Biologics, Inc.: Employee, Salary; H. Whalen, Synthetic Biologics, Inc.: Employee, Salary; C. Le, Synthetic Biologics, Inc.: Employee, Salary; C. Da Costa, Synthetic Biologics, Inc.: Employee, Salary; J. Sliman, Synthetic Biologics, Inc.: Employee, Salary.